KAJI EKSPERIMENTAL SISTEM PENYIMPANAN BIOGAS DENGAN METODEPENGKOMPRESIAN DAN PENDINGINAN PADA TABUNG GAS SEBAGAI BAHAN BAKAR PENGGANTI GAS LPG - Fadli, Dian; Irsyad, Muhammad; Susila, M.Dyan (FT UNILA, 2013)
The potential of biogas from cattle dung in Lampung province is big enough that 227 792 kg / day based on the number of cattle and buffalo tails as much as 742.8. During this shelter biogas only placed in plain tubes which are then piped into the pipeline for use as lighting and gas stove. This study intends to outline the principles of storage technology in LPG cylinder biogas, biogas and testing by cooling and compressing. Based on the results of testing at constant pressure 6 bar with the lowest temperature variation 7 ° C the amount of mass is 36.4 grams stored while based on calculations using the ideal gas law mass quantities stored at a temperature of 7 ° C is 36.7 grams. And the highest temperature of 10 ° C the amount of stored mass of 34 grams, while based on the calculation of the amount of mass stored at a temperature of 10 ° C for 36 grams. This is an effective way to increase the density of the biogas. And a beginning reference for researchers who want to conduct research on biogas biogas ÙÎ÷Sõanging to a liquid phase. Keywords: Biogas, storage systems, compressing and cooling, Ideal Gas